Flexibility and torsional resistance of three nickel-titanium retreatment instrument systems - Hussne, R. P.; Braga, L. C.; Berbert, Fabio Luiz Camargo Villela [UNESP]; Buono, V. T. L.; Bahia, M. G. A. (Wiley, 2011)
Aim To assess the dimensional characteristics, flexibility and torsional behaviour of nickel-titanium retreatment instruments. Methodology Using image analysis software and high-resolution digital images, the instrument length, tip angle, diameter at 3mm from the tip and the distance between the blades (pitch length) of the following eight instruments were measured (n=12 for each measurement parameter): the ProTaper Universal retreatment (PTU-R) D1, D2 and D3 instruments; the R-Endo R1, R2 and R3 retreatment instruments; and the Mtwo retreatment (Mtwo-R) sizes 25 and 15 retreatment instruments. Maximum torque and the angular deflection at fracture as well as the bending moment at 45° were measured (n=12) according to the International Standards Organisation (ISO) specification number 3630-1. Data were analysed using the analysis of variance (α=0.05). Results The length of the active part of the instruments was found to vary according to the depth of the canal into which they were designed to reach. The pitch length also increased along the active length. The PTU-R D1 and the Mtwo-R instruments had active tips. Measurements of the bending moment at 45° revealed that the Mtwo-R 15 instrument was the most flexible, whereas the PTU-R D1 was the least flexible. The maximum torque tended to increase as the instrument diameter at 3mm from the tip increased, whereas the angular deflection at fracture varied in the opposite direction. Conclusions The geometrical characteristics of the retreatment instruments and their flexibility and torsion behaviour were consistent with their intended clinical application. © 2011 International Endodontic Journal.
Keywords: Endodontic retreatment instruments; Flexibility; Nickel-titanium; Torsional resistance; dental alloy; nickel; titanium; titanium nickelide; dental care; dental equipment; endodontics; equipment design; instrumentation; mechanical torsion; pliability; retreatment; Dental Alloys; Dental Instruments; Dental Stress Analysis; Equipment Design; Nickel; Pliability; Retreatment; Root Canal Preparation; Titanium; Torsion, Mechanical